Am MetLife Takaful Berhad / Nazirah Yaacob - Yaacob, Nazirah (Faculty of Business and Management, 2023)
As a requirement for students to complete the study in Bachelor of Business Administration (Hons) Finance program, students are required to perform Industrial Training under the course of MGT666 in their final semester. The industrial training will be carried out for 24 weeks, beginning in March, 2023 until August, 2023. This internship course acts as a hands-on training ground for students to get real-world experience, workplace skills, and a sense of responsibility in handling responsibilities given to them by the employer. I have successfully finished this Industrial Training Report at the organization w here I have worked, headquarters of Am MetLife Takaful Berhad, within the department of Finance. I began working for this organization in March 2023 and in my opinion, it is an excellent place to begin a career and enhance m y talents. Am MetLife Takaful provides a wide range of takaful products supplied through the nationwide Am MetLife branch office network of the AmBank Group. A written report is one of the necessary for finishing the course. To prepare this report, I reflect on m y experience and insights on m y working expertise in relation to what I have learnt throughout m y study such as financial management and strategic management. It also contains concise information on what I have gained throughout the industrial training in preparing m e for m y future career. I've covered every significant aspect of this organization that I experienced during m y internship in m y report. I provided information on the company's profile in the first section. In the second section, I described my internship experience. I provided some analysis on Am MetLife Takaful, emphasizing its Strengths, Weaknesses, Opportunities, and Threats, incorporating the PESTEL analysis framework element. This report is then followed discussions and recommendations while conclusions are presented in the last section of my report.